PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, AUDITOR SWITCHING DAN PANDEMI COVID-19 TERHADAP AUDIT DELAY. - Hani Frimmantuti (2022)
This study is a quantitative study that aims to examine the effect of firm size, financial distress, auditor switching and the COVID-19 pandemic on audit delay. This study uses data from the financial statements of food and beverages companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The selection of sample criteria was carried out using a purposive sampling technique with predetermined criteria and obtained a total of 66 data samples from 22 food and beverages companies. Hypothesis testing in this study using multiple linear regression analysis with SPSS 24 program with a significance level of 5% (0.05). The results of this study indicate that 1) firm size has a negative and significant effect on audit delay; 2) financial distress has no effect on audit delay; 3) auditor switching has no effect on audit delay; 4) the COVID-19 pandemic has no effect on audit delay and there is no difference in audit delay before the COVID-19 pandemic and after the COVID-19 pandemic.